Privacy and Identity Management. Facing up to Next Steps: 11th IFIP WG 9.2, 9.5, 9.6/11.7, 11.4, 11.6/SIG 9.2.2 International Summer School, Karlstad, Sweden, August 21-26, 2016, Revised Selected Papers - Lehmann, Anja; Whitehouse, Diane; Fischer-Hubner, Simone; Fritsch, Lothar; Raab, Charles (Privacy and Identity Management. Facing up to Next Steps 11th IFIP WG 9.2, 9.5, 9.6/11.7, 11.4, 11.6/SIG 9.2.2 International Summer School, Karlstad, Sweden, August 21-26, 2016, Revised Selected Papers, 2017)
This book contains a range of invited and submitted papers presented at the 11th IFIP WG 9.2, 9.5, 9.6/11.7, 11.4, 11.6/SIG 9.2.2 International Summer School, held in Karlstad, Sweden, in August 2016.The 17 revised full papers and one short paper included in this volume were carefully selected from a total of 42 submissions and were subject to a two-step review process. The papers combine interdisciplinary approaches to bring together a host of perspectives: technical, legal, regulatory, socio-economic, social, societal, political, ethical, anthropological, philosophical, and psychological.The paper 'Big Data Privacy and Anonymization' is published open access under a CC BY 4.0 license at link.springer.com.